AUDIT ENERGI UNTUK PENCAPAIAN PENGHEMATAN PENGGUNAAN ENERGI LISTRIK DI PT. GRAHA SARANA DUTA II DENPASAR - Sylvi Oktavia Ginting; Ida Bagus Gede Manuaba; A A Gede Maharta Pemayun (Jurnal SPEKTRUM, 2022)
Energy audit is a technique used to determine the amount of energy use in a buildingand to find various energy-saving solutions or opportunities. In this study, the energy audit wasconducted at PT. Graha Sarana Duta II Denpasar which is located on Jl. Serma Gede No. 13,Dauh Puri Klod, Denpasar. Based on the existing conditions, the level of Energy ConsumptionIntensity (IKE) obtained before the audit was carried out was 245.22 kWh/m2/year or 20.43kWh/m2/month which according to ESDM No. 13/2012, Air-conditioned buildings are in thewasteful category. In this study, the energy audit focuses on the lighting system and airconditioning system. The method used in this research is to calculate and analyze theconsumption of electrical energy in the lighting system and air conditioning system. After doingthe research, it can be seen the energy saving opportunities (PHE) in PT. Graha Sarana Duta IIDenpasar by replacing the TL and SL lamps using LED lamps and requiring room users to turnoff the air conditioner when the room is not in use, the result is savings 11,4% in electricalenergy use, where the IKE after the audit is 18.1 kWh/m2/month. The office can also save thecost of using electrical energy, which is Rp. 3,170,394,- every month.